2020
DOI: 10.1177/1747954120953523
|View full text |Cite
|
Sign up to set email alerts
|

The classification in Para swimming: Analysis of a Paralympic champion’s withdraw case

Abstract: This study compared the in-water bilateral leg kick speed difference between a Paralympic and an Olympic athlete. The Paralympic (former S10) was not eligible after his reclassification in 2019, whereas the Olympic was a semi-finalist in 50 m freestyle in Rio 2016. Kick performance was assessed by a speedometer in one push-off ∼15 m maximal kick sprint. Ten complete cycles were analyzed, and the average speed of each leg in each cycle was calculated. Computerized planimetry assessed plantar feet areas. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In the para swimming context, the speed curve analysis was used to establish knowledge about classification. For instance, Barbosa et al 6 utilized the in-water bilateral leg kick speed difference to provide insights into the classification process of a former Paralympic swimmer. The authors concluded that the impact of his impairment on kick performance differs when using quantitative and qualitative assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In the para swimming context, the speed curve analysis was used to establish knowledge about classification. For instance, Barbosa et al 6 utilized the in-water bilateral leg kick speed difference to provide insights into the classification process of a former Paralympic swimmer. The authors concluded that the impact of his impairment on kick performance differs when using quantitative and qualitative assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The in‐water technical assessment, for example, consists of athletes swimming multiple distances at different speeds as classifiers subjectively assign separate body segments a score from 0 to 5, with lower numbers indicating greater activity limitation. The efficacy of the subjective assessment of activity limitation and the weighting and aggregation of point scores for different body segments has been questioned 2,4,5 . Research that identifies quantitative tests that objectively measure the impact of impairment on the determinants of swimming performance can help to advance Para swimming classification.…”
Section: Introductionmentioning
confidence: 99%